Investigating the use of ultrasonography for the antenatal diagnosis of structural congenital anomalies in low-income and middle-income countries: a systematic review - Nana Adofo-Ansong; Laurence Isaaya Ntawunga; Maame Tekyiwa Botchway; Ann Horton Kelly (BMJ Paediatrics Open)
Background Congenital anomalies are the fifth leading cause of under-5 mortality globally. The greatest burden is faced by those in low/middle-income countries (LMICs), where over 95% of deaths occur. Many of these deaths may be preventable through antenatal diagnosis and early intervention. This systematic literature review investigates the use of antenatal ultrasound to diagnose congenital anomalies and improve the health outcomes of infants in LMICs.Methods A systematic literature review was conducted using three search strings: (1) structural congenital anomalies; (2) LMICs; and (3) antenatal diagnosis. The search was conducted on the following databases: Medline, Embase, PubMed and the Cochrane Library. Title, abstract and full-text screening was undertaken in duplicate by two reviewers independently. Consensus among the wider authorship was sought for discrepancies. The primary analysis focused on the availability and effectiveness of antenatal ultrasound for diagnosing structural congenital anomalies. Secondary outcomes included neonatal morbidity and mortality, termination rates, referral rates for further antenatal care and training level of the ultrasonographer. Relevant policy data were sought.Results The search produced 4062 articles; 97 were included in the review. The median percentage of women receiving an antenatal ultrasound examination was 50.0% in African studies and 90.7% in Asian studies (range 6.8%–98.8%). Median detection rates were: 16.7% Africa, 34.3% South America, 34.7% Asia and 47.3% Europe (range 0%–100%). The training level of the ultrasound provider may affect detection rates. Four articles compared morbidity and mortality outcomes, with inconclusive results. Significant variations in termination rates were found (0%–98.3%). No articles addressed referral rates.Conclusion Antenatal detection of congenital anomalies remains highly variable across LMICs and is particularly low in sub-Saharan Africa. Further research is required to investigate the role of antenatal diagnosis for improving survival from congenital anomalies in LMICs.PROSPERO registration number CRD42019105620.